Implementation of the milestones communication approach for patients with limited prognosis: evaluation of intervention fidelity - Bossert, Jasmin; Wensing, Michel; Thomas, Michael; Villalobos Bollen, Matthias Americo; Jung, Corinna; Siegle, Anja; Hagelskamp, Laura; Deis, Nicole; Jünger, Jana; Krug, Katja (BMC palliative care, 2020)
Despite improvements in diagnostics and therapy, the majority of lung tumours are diagnosed at advanced stage IV with a poor prognosis. Due to the nature of an incurable disease, patients need to engage in shared decision making on advance care planning. To implement this in clinical practice, effective communication between patients, caregivers and healthcare professionals is essential. The Heidelberg Milestones Communication Approach (MCA) is delivered by a specifically trained interprofessional tandem and consists of four milestone conversations (MCs) at pivotal times in the disease trajectory. MC 1 (Diagnosis): i.e. prognosis; MC 2 (Stable disease): i.e. prognostic awareness; MC 3 (Progression): i.e. reassessment; MC 4 (Best supportive care): i.e. end of treatment. In between MCs, follow-up calls are carried out to sustain communication. This study aimed to assess to what extent the MCA was implemented as planned and consolidated in specialized oncology practice.
Gesehen am 26.03.2020